Density-functional investigation of the rhombohedral to simple-cubic phase transition of arsenic - Silas,P; Yates,JR; Haynes,PD (PHYS REV B, 2008)
We report on our investigation of the crystal structure of arsenic under compression, focusing primarily on the pressure-induced A7 -> simple-cubic (sc) phase transition. The two-atom rhombohedral unit cell is subjected to pressures ranging from 0 to 200 GPa. For each given pressure, cell lengths and angles, as well as atomic positions, are allowed to vary until the fully relaxed structure is obtained. We find that the nearest- and next-nearest-neighbor distances give the clearest indication of the occurrence of a structural phase transition. Calculations are performed using the local-density approximation (LDA) and the Perdew-Burke-Ernzerhof and Perdew-Wang generalized gradient approximations (GGA-PBE and GGA-PW91) for the exchange-correlation functional. The A7 -> sc transition is found to occur at 21 +/- 1 GPa in the LDA, at 28 +/- 1 GPa in the GGA-PBE, and at 29 +/- 1 GPa in the GGA-PW91. No volume discontinuity is observed across the transition in any of the three cases. We use k-point grids as dense as 66x66x66 to enable us to present reliably converged results for the A7 -> sc transition of arsenic.